DEVELOPMENT OF MODIFIED DOMINO CARD LEARNING MEDIA IN SOCIAL SCIENCE SUBJECTS ON THE MATERIAL TYPES OF WORK FOR GRADE III STUDENTS OF MADRASAH IBTIDAIYAH - Tutut Handayani; Amir Hamzah; Dini Saskia (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
This research aims to produce modified domino card learning media in Social Science subjects on the material types of work for grade III students of Madrasah Ibtidaiyah (MI). This is Research & Development analysis with the Tessmer model which consists of self-evaluation, expert review, one-to-one, and small group. Furthermore, eight students of grade III MI Quraniah 8 Palembang participated. The results show that the modified domino card learning media in social studies subjects is very valid. This is because the validation of design and material experts, as well as linguists, which obtained an average score of 95, 89, and 80, was categorized as very valid. Moreover, the average score of 91 indicates that this learning media is highly practical. It can be concluded that the modified domino card learning media is valid and practical.